Potential Alternative to Nitrite in Roasted Lamb for Sensory Attributes: Atmospheric Nonthermal Plasma Treatment - Ruixia Chen; Dequan Zhang; Huan Liu; Zhenyu Wang; Teng Hui (Foods, 2021)
Reducing or replacing sodium nitrite without compromising the sensory attributes of meat products has always been a focus of the meat industry. In this study, five treatments, CT (without nitrite and plasma treatment), NT (with nitrite treatment), PT15, PT30, and PT45 (without nitrite and with plasma treatment for 15, 30, and 45 min, respectively), were designed to investigate the effect of atmospheric nonthermal plasma treatment replacing nitrite on the sensory attributes of roasted lamb. Results showed that PT45 decreased the residual nitrite of roasted lamb by 30% compared with NT, and nitrite was not detected in the PT15 and PT30 samples. The inhibition effect of plasma treatment on the lipid oxidation reached values from 86.69% to 89.89% compared with NT. Compared with CT, the redness of plasma-treated samples was increased by 9.30% to 31.40%, and the redness of NT samples was increased by 30.87%. In addition, the volatile compounds (OAVs > 1) of the PT30 sample were higher than those of the NT sample. The overall sensory score of the PT30 sample was higher than that of the CT sample and was similar to that of the NT samples. In conclusion, the sensory attributes of roasted lamb were enhanced by plasma treatment, and the 30 min plasma treatment is recommended.